In silico analysis of the binding of anthelmintics to Caenorhabditis elegansP-glycoprotein 1. Issue 3 (December 2016) - David, Marion A.; Orlowski, Stéphane; Prichard, Roger K.; Hashem, Shaima; André, François; Lespine, Anne
Abstract: Macrocyclic lactones (ML) are important anthelmintics used in animals and humans against parasite nematodes, but their therapeutic success is compromised by the spread of ML resistance. Some ABC transporters, such asp -glycoproteins (Pgps), are selected and overexpressed in ML-resistant nematodes, supporting a role for some drug efflux proteins in ML resistance. However, the role of such proteins in ML transport remains to be clarified at the molecular level. Recently, Caenorhabditis elegans Pgp-1 (Cel-Pgp-1) has been crystallized, and its drug-modulated ATPase function characterized in vitro revealed Cel-Pgp-1 as a multidrug transporter. Using this crystal structure, we have developed an in silico drug docking model in order to study the binding of ML and other anthelmintic drugs to Cel-Pgp-1. All tested ML bound with high affinity in a unique site, within the inner chamber of the protein, supporting that ML may be transported by Cel-Pgp-1. Interestingly, interacting residues delineate a ML specific fingerprint involving H-bonds, including T1028. In particular, benzofurane and spiroketal moieties bound to specific sub-sites. When compared with the aglycone ML, such as moxidectin and ivermectin aglycone, avermectin anthelmintics have significant higher affinity for Cel-Pgp-1, likely due to the sugar substituent(s) that bind to a specific area involving H-bonds at Y771. Triclabendazole, closantel and emodepside bound with good affinities to different sub-sites in the inner chamber, partially overlapping with the ML binding site, suggesting that they could compete for Cel-Pgp-1-mediated ML transport. In conclusion, this work provides novel information on the role of nematode Pgps in transporting anthelmintics, and a valuable tool to predict drug-drug interactions and to rationally design new competitive inhibitors of clinically-relevant nematode Pgps, to improve anthelmintic therapeutics. Graphical abstract: Ivermectin (red spheres) binding to Cel-Pgp-1 (blue ribbon: N-term, yellow ribbon: C-term). Highlights: Cel-Pgp-1 cristal provides a valuable tool to study anthelmintic interactions. Cel-Pgp-1 recognizes a broad panel of anthelmintics, including macrocyclic lactones. Cel-Pgp-1 is predicted to transport MLs and contribute to anthelmintic resistance. Sugars in avermectins increase the affinity to Cel-Pgp-1 compared with moxidectin. These data provide a basis for modelling ABC homologs in parasitic nematodes.